Cross Talk Between Macrophages and Podocytes in Diabetic Nephropathy: Potential Mechanisms and Novel Therapeutics - Siming Yu; Zehui Han; Chunsheng Li; Xinxin Lu; Yue Li; Xingxing Yuan; Dandan Guo (Mediators of Inflammation)
Diabetic nephropathy (DN) is a leading cause of chronic kidney disease and end-stage renal failure worldwide. Podocytes, essential components of the glomerular filtration barrier (GFB), are profoundly affected in the diabetic milieu, resulting in structural and functional alterations. Concurrently, macrophages, pivotal innate immune cells, infiltrate the diabetic kidney and exhibit diverse activation states influenced by the local environment, playing a crucial role in kidney physiology and pathology. This review synthesizes current insights into how the dynamic cross talk between these two cell types contributes to the progression of DN, exploring the molecular and cellular mechanisms underlying this interaction, with a particular focus on how macrophages influence podocyte survival through various forms of cell death, including apoptosis, pyroptosis, and autophagy. The review also discusses the potential of targeting macrophages to develop more effective treatments for DN.